Digital library of historical buildings in Malaysia (DLHB) / Woo Wei Wei - Woo, Wei Wei (2002)
The Digital Library of Historical Buildings in Malaysia (DLHB) is developed with its goal to offer historical resources on Malaysian buildings that is comprehensive and could be used by anyone, anywhere and at anytime. The objective of developing Digital Library of Historical Buildings is to provide secondary students with a convenient method to access specific local historical information from the digital library in completing their history projects or assignments. It is hoped that the implementation of DLHB could provide better maintenance of archival materials and user information. Teachers can be involved as collaborators to enrich the repository content and also manage previously submitted project reports which are excellent. Finally DLHB would contribute to enrich local content of historical information system. Functions that are provided by the DLHB system are search and retrieve, indexing list, registration, feedback, bulletin and the administration tools to upload, modify and delete information. The database of DLHB is a multimedia database which includes electronic text, scanned text, images, audio and video. The limitation of this system is that the database covers only some selected school buildings and tall buildings in Kuala Lumpur and Selangor. DLHB is developed under Windows 2000 as the server platform and using internet Information Server 5.0 as the web server. Apart from that, SQL Server 7.0 is used as the database management system. Programming tools selected for the development of DLHB arc HTML, ASP, and JavaScript. On the other hand, Microsoft Visual InterDev, Macromedia Dreamweaver and Adobe Acrobat are used as the software applications in developing the system. During implementation, three areas of development were taken into consideration, which are programming development, database development and web page design. Every single task has its own problem but was solved by reading reference books and seeking help from colleagues. In the stage of testing and evaluation, different testing techniques were applied to ensure that the system fulfilled its functional and non-functional requirements. In addition, user acceptance test is carried out in a real environment in one of the selected secondary school in Petaling Jaya. It is hoped that the Digital Library of Historical Buildings (DLHB) will serve its purpose in shaping and contributing towards the current smart learning environments in Malaysia.